Student Leadership in Pesantren Governance: The Role of Student Organizations in Fostering Congregational Prayer and Religious Character - Siti Hawa; Ngantori Ngantori (IQRO: Journal of Islamic Education, 2026)
This study examines the role of the Jarinabi Islamic Boarding School Student Organization (OPJN) in fostering congregational prayer among male students as part of student leadership within pesantren governance. The study was conducted because student organizations are expected to contribute not only to administrative responsibilities but also to the development of religious character through structured guidance and supervision. A qualitative descriptive approach was employed. Data were collected through observations, semi-structured interviews, and documentation involving boarding school leaders, supervisors, OPJN administrators, and male students selected purposively. The findings reveal that OPJN performs strategic functions in organizing, supervising, mentoring, and evaluating congregational prayer through a coordinated and continuous guidance system. These functions strengthen religious culture, improve students' discipline and responsibility, and facilitate the internalization of Islamic values in daily pesantren life. The study concludes that student organizations constitute an integral component of the pesantren educational management system by linking student leadership with religious character development through systematic worship guidance. This study contributes to the field of Islamic educational management by demonstrating how student organizations function as governance mechanisms that reinforce religious culture, strengthen student leadership, and support sustainable character development in Islamic boarding schools.